2020
DOI: 10.3390/ijms21176082
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chloroplast Gene Expression in Plant Responses to Environmental Stress

Abstract: Chloroplasts are plant organelles that carry out photosynthesis, produce various metabolites, and sense changes in the external environment. Given their endosymbiotic origin, chloroplasts have retained independent genomes and gene-expression machinery. Most genes from the prokaryotic ancestors of chloroplasts were transferred into the nucleus over the course of evolution. However, the importance of chloroplast gene expression in environmental stress responses have recently become more apparent. Here, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 131 publications
(164 reference statements)
0
57
0
Order By: Relevance
“…However, this review will mainly focus on the photoreceptors. Readers may refer to Fernandez and Strnad (2008); Crawford, Lehotai, and Strand (2018) and Zhang, Zhang, Li, and Lu (2020) for a broader description of the role of plastids in responses to stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, this review will mainly focus on the photoreceptors. Readers may refer to Fernandez and Strnad (2008); Crawford, Lehotai, and Strand (2018) and Zhang, Zhang, Li, and Lu (2020) for a broader description of the role of plastids in responses to stress.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue “Organelle Genetics in Plants,” 11 articles were accepted with four reviews and seven original research articles covering outstanding advances in different chloroplast and plant mitochondria research fields ( Table 1 ). These works focus on topics related to organellar gene expression (OGE) (chloroplast RNA editing in soybean [ 5 ], mitochondria RNA editing and intron splicing in soybean during nodulation [ 6 ] and the roles of transcriptional and post-transcriptional regulation of OGE in responses to environmental stress [ 7 , 8 ]); the analysis of nuclear integrants of mitochondrial DNA (NUMTs) or plastid DNA (NUPTs) [ 9 ]; the sequencing and characterization of organellar genomes (the mitogenomes of common bean [ 10 ] and four Trifolium species [ 11 ], and the chloroplast genomes (plastomes) of Trentepohlia odorata [ 12 ], three Utricularia amethystina morphotypes [ 13 ], and three plant parasitic Macrosolen species [ 14 ]); and finally, the most recent advances in plastid genome engineering [ 15 ]. In this editorial, we sum up the main findings of these eleven insightful manuscripts.…”
mentioning
confidence: 99%
“…Two reviews are about the emerging importance of OGE processes in plant responses to environmental stress. Quesada and Robles [ 7 ] and Zhang et al [ 8 ] compile the results hitherto published from analyzing plant mutants, mainly in Arabidopsis and rice, revealing a connection between OGE and tolerance to environmental stress. Our review [ 7 ] summarizes the works reporting the phenotypic and molecular analyses of plant mutants exhibiting altered sensitivity to salinity that are affected in nuclear genes involved in OGE regulation at transcriptional or post-transcriptional levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that PSII is generally more sensitive to temperature stress [20] compared to PSI [21]. Indeed, plants deal with environmental stresses by regulating the expression of some stress-responsive genes [22]. Heat stress induces alterations in protein factors that are involved in de novo assembly and/or degradation and turnover of the of PSII reaction center proteins.…”
Section: Introductionmentioning
confidence: 99%